Analisis Perubahan Lahan Ruang Terbuka Hijau di Kecamatan Tegalrejo dan Kecamatan Wirobrajan Kota Yogyakarta Tahun 2007-2017 - Taurizina, Inggit; , Drs. Munawar Cholil, M.Si (2017)
the availability of land and will have an impact on the existence of open green space in the urban area. The needs and the demands of public life influence land use change of open green space that occurs. The purpose of this research are : 1) analyzing the comparison of open green space land use change between Tegalrejo district and Wirobrajan District during 2007 until 2013 2) analyzing the pattern of open green space land use change between Tegalrejo district and Wirobrajan District during 2007 until 2013. This research using Survey Method with purposive sampling technique for analyzing the open green space land use change during 2007 until 2013. Data processing analysis using overlay and data analysis using descriptive and comparative description of the table. The result of this research show that open green space land use change at Tegalrejo dsitrict occur in Kelurahan Bener and Kelurahan Kricak with agricultural area like rice fields and garden reduced quite significantly. Open green space land use change at Wirobrajan district occur in Kelurahan Pakuncen and Kelurahan Patangpuluhan with sleeping land and garden yard. Land use change at Tegalrejo and Wirobrajan district wich dominate is building. Pattern change of open green sapce area that occur in Tegalrejo district consist of 11 pattern land use change, whileat Wirobrajan district consist of 7 pattern land use change. Keywords : Open Green Space, Land Use Change, Land Use Change Pattern.